Peran Pendidikan Agama Islam dalam Meningkatkan Nilai Islami Keluarga dan Masyarakat - Azhari, Abdul; Qori Amanda, Rakhel (Integrasi: Jurnal Studi Islam dan Humaniora, 2024)
Islamic religious education has a very important role in shaping individual personality and morals, both in the family and in society. However, there are many challenges and problems faced in implementing Islamic religious education, both at the family and wider community levels. The basis for this research uses library research using references from several journals and books covering Islamic religious education in the family and society. Based on this article, it can be concluded that Islamic religious education has a broad impact, not only limited to the formation of individual character, but also forms the basis of morals and ethics in society.